Examining intensity and types of interagency collaboration between child welfare and drug and alcohol service providers. (August 2015) - He, Amy S.
Abstract: The co-occurrence of child maltreatment and caregiver substance use disorders (SUDs) is a pervasive problem, with an estimated two thirds of child welfare (CW) systems cases involving SUDs. Interagency collaboration between CW and drug and alcohol service (DAS) providers shows promise in improving connections to and delivery of SUD services for CW-involved families. However, interagency collaboration between CW and DAS providers continues to be difficult to achieve and little is known about organizational characteristics and contexts that influence collaboration between these two entities. Using data from the second cohort of families from the National Survey of Child and Adolescent Well-Being, this study examined national trends in interagency collaboration between CW and DAS providers and organizational factors that influence the nature and intensity of interagency collaboration. Results indicated that collaboration intensity was greater for CW agencies that reported increased caseloads and those located in more populated counties. However, collaboration intensity decreased for CW agencies located in counties with higher child poverty. Study findings have implications for policy leaders and directors of CW agencies throughout the United States, especially because collaborating with DAS providers may increase CW agencies' organizational capacity and relieve job stress related to high caseloads. Development of strategies that spur engagement in more intense and multiple types of collaboration between CW agencies and DAS providers has the potential to relieve service burden on CW staffs and expedite service delivery to CW-involved families dealing with SUDs.